2017
DOI: 10.3349/ymj.2017.58.5.994
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Multiparametric and Biparametric MRI in First Round Cognitive Targeted Prostate Biopsy in Patients with PSA Levels under 10 ng/mL

Abstract: PurposeTo determine the efficacy of cognitive targeted prostate biopsy using biparametric magnetic resonance imaging (b-MRI) for patients with prostate-specific antigen levels under 10 ng/mL.Materials and MethodsWe reviewed data from 123 consecutive patients who underwent cognitive targeted prostate biopsy using prostate MRI. Of these patients, the first 55 underwent prostate biopsy using multiparametric MRI (mp-MRI), and the remaining 68 underwent prostate biopsy using b-MRI. For b-MRI, we generated T2 weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 19 publications
0
27
0
Order By: Relevance
“…Thestrup et al [83] reported similar accuracies of bpMRI and mpMRI in detecting csPCa, although without providing any formal statistical comparisons. Lee et al [84] compared two cohorts undergoing mpMRI and bpMRI for a suspicion of PCa and then receiving visual MRI-TBx in addition to standard systematic biopsy. The authors reported a similar detection of csPCa among men who had suspicious lesions in the bpMRI and mpMRI groups (63% and 62%, respectively).…”
Section: Biparametric Mri Versus Mpmrimentioning
confidence: 99%
“…Thestrup et al [83] reported similar accuracies of bpMRI and mpMRI in detecting csPCa, although without providing any formal statistical comparisons. Lee et al [84] compared two cohorts undergoing mpMRI and bpMRI for a suspicion of PCa and then receiving visual MRI-TBx in addition to standard systematic biopsy. The authors reported a similar detection of csPCa among men who had suspicious lesions in the bpMRI and mpMRI groups (63% and 62%, respectively).…”
Section: Biparametric Mri Versus Mpmrimentioning
confidence: 99%
“…As we described in the previous studies, the overall detection rates of csPCa were not different between the mpMRI and bpMRI [17]. In addition, several studies used simple bpMRI for cost-effectiveness [15,[17][18][19]. bpMRI avoids additional cost, acquisition time, and side effects caused by contrast media.…”
Section: Discussionmentioning
confidence: 64%
“…found 11.9 min scanning time (and 15.7 min table time) for bpMRI and ±45 min for mpMRI [9]. This was confirmed by Dong Hoon Lee et al., who found an in-bore time of 15 min for bpMRI and 45 min for mpMRI [10]. Other authors found considerably shorter time differences between mpMRI and bpMRI.…”
Section: Benefits Of Omitting Dcementioning
confidence: 73%
“…reported additional costs of about € 56 for a 70-kg patient only for the contrast agent [11]. A Korean group calculated costs of about $ 600 for mpMRI and only $ 300 for bmMRI [10].…”
Section: Benefits Of Omitting Dcementioning
confidence: 99%